Review of Multiculturalism and Diversity in Applied Behavior Analysis, edited by Conners and Capell. Issue 2 (13th January 2022) - Jimenez‐Gomez, Corina; Beaulieu, Lauren
Abstract : Multiculturalism and Diversity in Applied Behavior Analysis: Bridging Theory and Application edited by Brian Conners and Shawn Capell is notable for being the first edited book in the field of behavior analysis focusing on the importance of cultural variables in the implementation of our science. Importantly, the contributors to this book come from a range of different cultural backgrounds, providing diverse perspectives when discussing cultural responsiveness. The topics included in this book range from a discussion of cultural variables, to issues relevant to clients from diverse cultural backgrounds, and proposed standards for practice. In addition to introducing the topic of diversity to behavior analysts, the book includes useful instructional tools such as activities, case studies, and a test bank.